Effectiveness Analysis of Canal Blocking in Sub-peatland Hydrological Unit 5 and 6 Kahayan Sebangau, Central Kalimantan, Indonesia - Yadi Suryadi; Indratmo Soekarno; Ivan Aliyatul Humam (Journal of Engineering and Technological Sciences, 2021)
The height of canal blocking has a significant influence on re-wetting peatland, depending on the canal’s distance. An effective canal in good condition has to raise the groundwater table to -0.4 m below ground level according to the Indonesian Ministry of Environment and Forestry (MENLHK). The effectiveness of different canal blockings was modeled by Freewat software with variation of canal distance (200 m, 250 m, 300 m, 350 m, and 400 m) and blocking height (0.2 m, 0.3 m, 0.4 m, 0.5 m, 0.6 m). This simulation was carried out using recharge and evapotranspiration data covering 20 years. The input of the conductivity value was done using 50 m/day according to the calibration. From the modeling, 0.6 m high canal blockings give a satisfactory result at every canal distance. The study took place during the annual dry season, when recharge was almost zero and average evapotranspiration was 6 mm/day. Adjusting the canal blocking to a maximum of 0.6 m and the canal distance to 400 m, the groundwater table slowly rose 0.38 m and it took 30 days to reach full-re-wetting capacity. This study revealed that the effectiveness of canal blocking is directly related to evapotranspiration and recharge, which has a positive correlation with the groundwater rise and the re-wetting period.